Construction and performance of an instrumented slope under capillary barrier systems - Hua, Chai Juay. (2012)
Rainfall-induced landslide is one of the most destructive natural disasters that can jeopardize public safety and lead to costly repair works. This natural disaster occurs frequently in residual soil slopes in many tropical areas. Infiltrating water from rainfall events enter the slope, resulting in a decrease of matric suction due to an increase in pore-water pressure in the slope, which in turns reduce the shear strength of the soil.